The seasonal behavior of the refractive index of the ionosphere over the equatorial region - Yesil, A.; Karatay, S.; Sagır, S.; Kurt, K. (My University, 2013)
In this study, the seasonal behavior of the refractive index of the ionosphere over equator region is investigated both for collisional and collisionless cases by using the real geometry of Earth’s magnetic field for north hemisphere with respect to latitudes. It is observed that there is a harmony between the behavior of the electron density distribution and extra ordinary waves both for collisional and collisionless cases at hmF2 peak in the ionosphere.

Bu çalışmada, ekvator bölgesinde iyonosferin kırılma indisinin mevsimsel davranışı, dünyanın gerçek manyetik alan geometrisi kullanılarak hem çarpışmalı hemde çarpışmasız durumlarda, kuzey yarım küre için enleme göre çalışılmıştır. İyonsferin hmF2 (F2- bölgesinin tepe yüksekliği) de çarpışmalı ve çarpışmasız durum için elektron yoğunlu dağılımı ile exra-ordinary dalgnın davranışı arasında bir uyum olduğu görülmüştür
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ionosphere; Equator region; Refractive index; İyonosfer; Kırılma indisi; Ekvator bölgesi